GMAT Question of the Day - Daily to your Mailbox; hard ones only

It is currently 18 Jun 2019, 20:06

Close

GMAT Club Daily Prep

Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track
Your Progress

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

Not interested in getting valuable practice questions and articles delivered to your email? No problem, unsubscribe here.

Close

Request Expert Reply

Confirm Cancel

If (x^2 + 6x + 9) + 6(x+3) + 9 = 0, then x=

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  
Author Message
TAGS:

Hide Tags

 
Senior PS Moderator
User avatar
V
Joined: 26 Feb 2016
Posts: 3373
Location: India
GPA: 3.12
If (x^2 + 6x + 9) + 6(x+3) + 9 = 0, then x=  [#permalink]

Show Tags

New post 02 Nov 2018, 02:26
1
00:00
A
B
C
D
E

Difficulty:

  5% (low)

Question Stats:

85% (01:23) correct 15% (01:21) wrong based on 55 sessions

HideShow timer Statistics

If \((x^2 + 6x + 9) + 6(x+3) + 9 = 0\), then x=

(A) -6
(B) -3
(C) 0
(D) 3
(E) 6

_________________
You've got what it takes, but it will take everything you've got
Senior PS Moderator
User avatar
D
Status: It always seems impossible until it's done.
Joined: 16 Sep 2016
Posts: 751
GMAT 1: 740 Q50 V40
GMAT 2: 770 Q51 V42
GMAT ToolKit User Premium Member Reviews Badge
Re: If (x^2 + 6x + 9) + 6(x+3) + 9 = 0, then x=  [#permalink]

Show Tags

New post 02 Nov 2018, 02:49
2
On careful observation we notice that the expression inside the first paranthesis is square of \(x+3\)
\((x^2 + 6x + 9) + 6(x+3) + 9 = 0\)

Hence we can denote x+3 by a new variable t.

Expression becomes...
\(t^2+6t+9=0\)
\((t+3)^2=0\)
\(t=-3\)
Substitute back to get original variable
\(x+3=-3\)
\(x = -6\)

Hence Option (A) is our choice.

Best,
Gladi

pushpitkc wrote:
If \((x^2 + 6x + 9) + 6(x+3) + 9 = 0\), then x=

(A) -6
(B) -3
(C) 0
(D) 3
(E) 6

_________________
Regards,
Gladi



“Do. Or do not. There is no try.” - Yoda (The Empire Strikes Back)
CEO
CEO
User avatar
V
Joined: 12 Sep 2015
Posts: 3783
Location: Canada
Re: If (x^2 + 6x + 9) + 6(x+3) + 9 = 0, then x=  [#permalink]

Show Tags

New post 21 Feb 2019, 14:24
Top Contributor
pushpitkc wrote:
If \((x^2 + 6x + 9) + 6(x+3) + 9 = 0\), then x=

(A) -6
(B) -3
(C) 0
(D) 3
(E) 6


Alternatively, we can simplify and solve the given equation

GIVEN: (x² + 6x + 9) + 6(x+3) + 9 = 0
Expand left side to get: x² + 6x + 9 + 6x + 18 + 9 = 0
Simplify left side to get: x² + 12x + 36 = 0
Factor left side to get: (x + 6)(x + 6) = 0
So, it must be the case that (x + 6) = 0
If x + 6 = 0, then x = -6

Answer: A

Cheers,
Brent
_________________
Test confidently with gmatprepnow.com
Image
VP
VP
User avatar
P
Joined: 31 Oct 2013
Posts: 1375
Concentration: Accounting, Finance
GPA: 3.68
WE: Analyst (Accounting)
Re: If (x^2 + 6x + 9) + 6(x+3) + 9 = 0, then x=  [#permalink]

Show Tags

New post 21 Feb 2019, 15:39
pushpitkc wrote:
If \((x^2 + 6x + 9) + 6(x+3) + 9 = 0\), then x=

(A) -6
(B) -3
(C) 0
(D) 3
(E) 6


Given ,

\((x^2 + 6x + 9) + 6(x+3) + 9 = 0\)

\((x+3)^2 + 6(x + 3) = -9\)

(x+3) {(x + 3 + 6)} = -9

(x + 3) ( x + 9) = -9.

Now substitute values from answer.

Option A works.

x = -6.
GMAT Club Bot
Re: If (x^2 + 6x + 9) + 6(x+3) + 9 = 0, then x=   [#permalink] 21 Feb 2019, 15:39
Display posts from previous: Sort by

If (x^2 + 6x + 9) + 6(x+3) + 9 = 0, then x=

  new topic post reply Question banks Downloads My Bookmarks Reviews Important topics  


Powered by phpBB © phpBB Group | Emoji artwork provided by EmojiOne